THE FUNCTION OF COMMUNICATION IN THE ACTIVITIES OF THE TEACHING LEARNING PROCESS IN THE CLASS ON ACCOUNTING DEPARTMENT STUDENTS OF SEMARANG STATE POLYTECHNIC - Pandiya Pandiya; Nurul Hamida (Politeknik Negeri Semarang, 2022)
Teaching and Learning Process Activities in the classroom are an organizational communication activity. In organizational communication there will be a communication function; such as informative, regulatory, persuasive, integrative, recreational, argumentative, controlling, emotional expression, motivational, social and educational functions. This study aims to determine the function of communication in the teaching and learning process activities in the classroom for Accounting Department students of Semarang State Polytechnic. The data collection is done by delivering a questionnaire to the respondents. The respondents of this study consist of Accounting Department students of the Semarang State Polytechnic. The data of this study are more qualitative, i.e. descriptions of the characteristics of respondents and not much related to numbers. Sampling is carried out by purposive sampling, namely students from the Accounting Department who had taken the Business Communication course. This study also aims to systematically and accurately describe facts and characteristics about the function of communication in teaching and learning activities in the classroom for Accounting Department students of Semarang State Polytechnic. The results have showed that the level of frequency of application of the communication function in the teaching and learning process in the classroom gives a result of mean score 4.23 which means it has a very high frequency; while the percentage of the application of the communication function in the teaching and learning process in the classroom gives a result of mean score 3.79 which means it has a high percentage. These results are in line with the results of previous studies.